2012
DOI: 10.1007/s15010-012-0263-4
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus transmission through organ transplantation in north-eastern Italy: a case report and implications for pre-procurement screening

Abstract: This report emphasizes that transplant-acquired WNV neuroinvasive disease can be particularly severe. We suggest that pre-procurement screening of organ donors by testing blood with both WNV IgM capture ELISA and a sensitive nucleic acid testing should be adopted during the transmission season in the present Italian epidemiological setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Testing for WNV infection before organ donation was done in only one of the eight donors. Because of a high level of WNV infection in northeastern Italy, the Italian National Transplant Network instituted a surveillance program in 2008 to detect WNV in organ donors in northeastern Italy (24, 25). However, the blood of this tested organ donor was negative for WNV by nucleic acid amplification (NAT).…”
Section: Review Of Clinical Diagnostic and Therapeutic Features Of mentioning
confidence: 99%
“…Testing for WNV infection before organ donation was done in only one of the eight donors. Because of a high level of WNV infection in northeastern Italy, the Italian National Transplant Network instituted a surveillance program in 2008 to detect WNV in organ donors in northeastern Italy (24, 25). However, the blood of this tested organ donor was negative for WNV by nucleic acid amplification (NAT).…”
Section: Review Of Clinical Diagnostic and Therapeutic Features Of mentioning
confidence: 99%
“…Transmission of WNV between humans during blood transfusion and tissue and or organ transplantation has been recorded in the USA [22] and recently in Europe [23,24,25,26]. In order to increase the biological safety of blood and organ donations, a screening policy has been implemented [27,28] in areas where human cases of WNV related diseases are known to be present, since it is believed that at least 80% of the WNV infected population remains asymptomatic during the phase in which viral RNA is actually detectable in blood [3].…”
Section: Virus Detectionmentioning
confidence: 99%
“…It is worth mentioning that the investigation that followed the infection of four organ recipients from an infected donor, demonstrated that the donor had been probably infected through blood transfusion [140]. Currently, there is not any national policy that requires organ donors screening, but serious cases of neuroinvasive disease in recipients implies a need for ELISA and NAT testing of donors during transmission season [143]. In 2002; a 20-year-old WNV infected woman delivered at term a live infant with chorioretinits and severe cerebral abnormalities (white matter loss, focal cerebral destruction) that was positive for WNV-specific IgM and neutralizing antibodies [144].…”
Section: Wnv In Humansmentioning
confidence: 99%